Answer:
[tex]x=\frac{\sqrt{13}-7 }{18} ,x=\frac{-\sqrt{13}-7 }{18}[/tex]
Step-by-step explanation:
I'm not too good with the quadratic formula so I'm going to complete the square.
First divide everything by 9 and move the 1 to the other side.
[tex]x^2-\frac{7}{9}=-\frac{1}{9}[/tex]
Then take half of [tex]\frac{7}{9}[/tex] and square it and add it to both sides.
[tex]x^2-\frac{7}{9} +\frac{49}{324}=\frac{13}{324}[/tex]
Now you can factor it.
[tex](x-\frac{7}{18})^2=\frac{13}{324}[/tex]
Square root:
[tex]x-\frac{7}{18}=\frac{\sqrt{13} }{18}[/tex]
[tex]x=\frac{\sqrt{13}-7 }{18} ,x=\frac{-\sqrt{13}-7 }{18}[/tex]